Historie imunoterapie - od Coley toxinů ke kontrolním bodům imunitní reakce - Říhová, B; Šťastný, M (Klinicka onkologie, 2015)
Immunotherapy dates back to 1868 when German physicist Busch intentionally infected patients suffering from soft tissue sarcoma with erysipelas. Rapid tumor shrinkage was observed but response was only partial and tumor recurrence subsequently occurred. It was William B. Coley who in 1891 injected a patient with a soft tissue sarcoma with streptococcal cultures. Following a severe attack of erysipelas, the tumor underwent extensive necrosis and the patient remained diseasefree for eight years. The mixture of Streptococcus and other bacteria including Seratia marcescens, Staphylococcus and Escherichia coli was referred to as Coleys toxin and was used for the next 45 years. This first immunotherapy was replaced at the beginning of the 20th century by more exact radiotherapy and later on by first chemotherapy with yperit. However, immunotherapy is a treatment that uses patients own immune system to help fight cancer and as such has several advantages over other treatments. Thus, the next major milestones in immunotherapy came in the middle of the 80s as a) adoptive cell therapy relaying on patients tumor infiltrating lymphocytes, b) injection of recombinant cytokines such as rIL2, c) identification of the first tumorassociated antigens and d) development of tumor specific monoclonal antibodies. It was followed by dendritic cells vaccines. Tremendous progress has been made in the past two decades with regard to understanding the complex interactions between tumors and the immune system and developing innovative ways to manipulate the antitumor immune response. It is recently represented as blockage of immune checkpoint inhibitors.
Keywords: Neoplasms; Immunotherapy; dějiny 19. století; imunoterapie; Humans; nádory; History, 20th Century; dějiny 20. století; lidé; History, 19th Century